Microblog publicity and IPO underpricing - Chao Dou; Xue Yang; Xuejin Bai; Rui Sun (China Journal of Accounting Studies (CJAS), 2023)
Based on many cases of publicity using social media in the market, this paper empirically examines the damage of microblog publicity to market efficiency by using the sample of IPO companies. The results show that the companies posting microblogs during the IPO publicity period have higher IPO underpricing, and the more the number of microblogs, the richer the content, the higher the proportion of microblogs in the operating activities, the higher the IPO underpricing. These relationships are stronger in the enterprises with higher degree of information asymmetry and management valuing social media more. Furthermore, microblogs posted during the IPO period mainly influence investor sentiment, especially small investors. In addition, the short-term stock market performance of the companies posting microblogs is significantly worse. This paper provides a theoretical basis for standardizing the information disclosure behavior of listed companies using social media.
Keywords: 650; Microblog; publicity; IPO underpricing; investor sentiment